Investigating the Relationship between Research and Development Costs and Audit Fees - Morteza Malek Ghasemi, Ali Iranmanesh (International Journal of Control and Automation, 2020)
Research and development costs are a key factor in growth and development of firms and are essential to maintain competition, but such costs are mostly based on management judgment and thus can create opportunities for abuse. The aim of this study was to investigate the effect of research and development costs on audit fees. In this quasi-experimental and post-event (using past information) research, the statistical population consisted of all companies accepted in Tehran Stock Market between 2009 and 2015. A multivariate regression model was used to analyze data and to test the research assumption. The findings suggested a significant positive relationship between research and development costs and audit fees. Therefore, it is recommended that all beneficiaries pay much attention to research and development costs.